Fast RSA-type cryptosystem with public data of small size - Satake, Kenji; Kasahara, Masao (Electronics & communications in Japan. Part 3, Fundamental electronic science, 1997)
A very important public‐key cryptosystem, the RSA cryptosystem, was proposed by Rivest, Shamir, and Adleman in 1978. As it offers a high level of security and can also be used for digital signature purposes, it has been the subject of active research. Although it has many excellent features, it is well known that the RSA cryptosystem requires excessive encryption and decryption time because both operations require exponentiation and division. This paper presents fast encryption and decryption algorithms appropriate for an RSA cryptosystem using a particular form of the modulus n. The proposed method, designed to perform modular exponentiation, simplifies greatly the processing step of the operation, thereby enhancing speed. Applying this method to the RSA cryptosystem, it becomes possible to implement the cryptosystem with a reduced public‐key size. User interface is both simple and secure. It is necessary to consider the tradeoff between a practical cryptosystem and a secure cryptosystem. It is even possible to send cipher text using a small key size, perhaps twice the size of a telephone number, with a higher security level than that of the conventional DES‐type cryptosystem, with a key size of 56 bits. © 1997 Scripta Technica, Inc. Electron Comm Jpn Pt 3, 80(2): 24–34, 1997